Kebiasaan Mengkonsumsi Tuak dan Persepsi Sehat Masyarakat Desa Bukit Selamat Kecamatan Besitang Kabupaten Langkat Propinsi Sumatera Utara - Nina Fentiana (Universitas Batanghari Jambi, 2019)
Tuak is a traditional alcoholic beverage in North Sumatera area, especially in Batak Toba, containing 4% alcohol. Tuak made from coconut or palm stem and taken water then mixed with raru. Drinking tuak is part of tradition that has become hereditary in the village of Bukit Selamat and very difficult to remove from the customs of society. Though alcohol can cause serious health effects of drunkenness, weight gain, high blood pressure, decreased immune system, cancer, heart disease, respiratory problems and liver disorders. The objective of the study was to describe the drinking habits of tuak and healthy perception of Bukit Selamat Village community. The research type is descriptive using explorative method. The researcher was conducted in Bukit Selamat Village Kec. Besitang Langkat District by collecting data from 92 respondents. The habit of drinking of tuak of Bukit Selamat Village is weight category 84,8% with 55,4% classified as new drink of palm wine. People with negative healthy perception were 66.3%. There is a relationship between healthy perception with the habit of consuming tuak of Bukit Selamat Village community.